2003
DOI: 10.1583/1545-1550(2003)010<0987:icewpa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Initial Clinical Experience With Percutaneous Atherectomy in the Infragenicular Arteries

Abstract: Below-the-knee native vessel lesions and in-stent restenoses with a diameter of at least 2.5 mm can be treated successfully and safely with this new atherectomy catheter. Additional balloon angioplasty was necessary in only a few cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…28,29 Recently, Zeller and colleagues 29 reported outcomes of 33 patients (52 lesions) following plaque excision revascularization of belowknee lesions. Only 15 patients were identified as Rutherford category 5, and none was classified as category 6.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Recently, Zeller and colleagues 29 reported outcomes of 33 patients (52 lesions) following plaque excision revascularization of belowknee lesions. Only 15 patients were identified as Rutherford category 5, and none was classified as category 6.…”
Section: Discussionmentioning
confidence: 99%
“…5 Specifically, the monorail catheter design is advanced over a 0.014-inch guidewire, and upon device activation, the catheter pivots against the lesion, exposing a cutting blade rotating at 8000 rotations per minute. As the catheter is manually advanced across the lesion length, atherosclerotic tissue is excised and contained within a distal storage chamber.…”
Section: Procedural Detailsmentioning
confidence: 99%
“…8 The heterogeneity of the patients combined with the lack of a more specific working definition for CLI makes defining outcomes challenging. Factors that have been shown to negatively impact EVT outcomes include: the indication 9,10 for the procedure, lesion length, 5 Trans Atlantic Inter-Societal Consensus (TASC) classification, 11 runoff score, 12-15 occlusion vs stenosis, 5 renal failure, 13 and excessive or heavy calcification 16,17 (Table). Evaluating the impact of diabetes on EVT remains difficult because patients with diabetes more commonly have multiple adverse risk factors.…”
mentioning
confidence: 99%
“…13,22 Similarly, heavy lesion calcification portends technical failure. 16,17 Because patients with diabetes are more susceptible to developing more heavily calcified atherosclerotic arteries and tibial artery occlusive disease, it is intuitive that patients with diabetes would have lower technical success rates compared with patients without diabetes. In a retrospective review of infrainguinal endovascular interventions primarily in the femoropopliteal segment, Lazaris et al 23 found a decreased technical success rate in patients with diabetes, 81% compared to 93% (P ϭ .05) in patients without diabetes.…”
mentioning
confidence: 99%